ZAKAZ KONKURENCJI PO USTANIU STOSUNKU PRACY A TAJEMNICA PRACODAWCY - Malinowska, Monika (Zeszyty Prawnicze, 2017)
The Prohibition of Rivalry after Ending of Work Relation and Professional Secret Summary The prohibition of rivalry after ending work relations is becoming more and more popular instrument in polish economy used in various parts. Employees during doing their official duties have an access to miscellaneous information being more or less important to employer. An employer who doesn’t want to risk, signs an agreement of prohibition of rivalry with the employee, which bans him or her taking part in a competition activity during or after ending work relations. By signing the prohibition of rivalry the employer indirectly protects his professional secrets. Nevertheless, it’s neither main nor direct aim of this agreement. The prohibition of rivalry, according to the 1011 article of labor code, forbids taking competition activity against the employer or working for other subject. This prohibition can include not only period during work relation, but also determined time after ending of work relation as well, when the employee has an access to some crucial information, the leak of which could cause the damage to the employer (article 1011 of labor code). An employer drawing this agreement binds himself to pay a compensation to the employee for obeying the rules included in the agreement. A professional secret can be defined as a piece of information which leak could make the damage to the employer according to the 100 § 2 article of labor codex. It can be every information connected with employer’s activity which security is legitimized by his economic interest. The elementary duty of an employee is to keep such information in secret since breaking the duty of keeping it in discretion leads to punishments described in labor codex, including disciplinary dismissal. In case of causing any damage to the employer’s interest there is a compensative responsibility. Next step to explain the problem is an interpretation of the company’s secret, which is elucidated by act on elimination of unfair competition from 16.04.1993. This interpretation is important due to the fact that the legislator orders to the employee to obey the secrets of company in regards to other regulations (in article 100 § 2 point 4 of the labor codex). In accordance to the 11 article of this act, the secret of company is defined as information of technical, technological, information and organizational character which cannot be revealed to the public or any other information of economic value. In order to keep them in discretion a trader is obliged to take necessary actions, since they should guarantee the security of the secret and protect them from non-authorized people. The prohibition of rivalry after ending work relations wasn’t created directly to secure the secrets of the employer. Legislator clearly distinguished information considering the prohibition of rivalry from those considering the employer’s secrets. The agreement of the prohibition of rivalry leads only indirectly to protection of the employer’s secrets, because a legislator as a subject of prohibition didn’t indicate secrets, but a competition activity. A very important fact is that the agreement of the prohibition of rivalry is used also in these employments, where the employer is not the trader, but the not economically active object in a strict meaning. Besides, prohibition of rivalry is the agreement between both sides of employment, so the employer and the employee indicate the scope of duty on their own. A secret of the employer is protected in legislation in labor code, in act of elimination of unfair competition and other acts. Therefore the protection of both concepts is different and indicates that they are not the same as the employer who signs the prohibitions of rivalry after ending the work relation is protected anyway. The aim of prohibitions of rivalry is to protect fair competition, which is not preserved by other regulations. Employer doesn’t get ipso jure protection of information connected with fair competition which are not secrets. And this information is protected by the prohibition of rivalry after ending work relation.